Evaluation of the Effectiveness of Health Education on Menopause Symptoms and Knowledge and Attitude in Terms of Menopause - Tugce Koyuncu; Alaettin Unsal; Didem Arslantas (Springer, 2018)
This study was carried out to evaluate the effectiveness of health education on menopausal symptoms, knowledge, and attitudes about menopause. To evaluate the efficacy of a training program, information about menopausal symptoms, knowledge, and attitude toward menopause was collected before and after health education. After the health education intervention, it was determined that there was a decrease in the somatic and psychological subdimensions of the menopausal symptom evaluation scale and in the total score. Positive changes were observed in the levels of knowledge about menopause, and positive and negative emotional subscales of the menopause attitude assessment scale. It is concluded that health education is an effective method to positively change the perceived severity of menopausal symptoms and menopause-related level of knowledge and attitude.